Heterogenity of Amber and Komin in Shaping Settlement Pattern of Jayapura City (Komunitas, 2015)
Jayapura city is the capital of Papua province, located at the eastern end of Indonesia and the borders with neighboring countries, Papua New Guinea. From the results of population census in 2010 the population of the Jayapura city is 256.705 inhabitants with a number of indigenous people as much as 89.773 people (34.97%) and as many as 166.932 nonPapua population (65.03%).  This figure shows that in Jayapura city, the number of migrants is much more than the indigenous people.  The term amber and komin then appears that refers to the indigenous people of Papua (komin) and immigrants nonPapua (amber).  The high migration flows in Jayapura resulting diversity in socio-cultural and economic structure of the population.  This impacted on the formation of the population settlement patterns.  This paper discusses the ethnic heterogeneity in Jayapura city community in shaping the urban spatial pattern.  From the discussion, it is known that the existing settlements in Jayapura city consists of settlements indigenous peoples, settlements inhabited by a mixed population of Papua and nonPapua population, settlements inhabited by ethnic Papuans from outside the city of Jayapura and settlements inhabited by ethnic immigrants certain nonPapua. Settlement indigenous peoples still survive as indigenous settlements that have a spiritual religious meaning that must be maintained and protected. While the settlement of migrants Papua and nonPapua formed by some preferences, namely the ties of kinship, proximity to sources of livelihood (workplace) and social status.Kota Jayapura merupakan ibukota Provinsi Papua yang terletak di ujung timur Indonesia dan berbatasan dengan negara tetangga, Papua Nugini. Dari hasil sensus penduduk tahun 2010 jumlah penduduk Kota Jayapura adalah 256.705 jiwa dengan jumlah penduduk asli Papua sebanyak 89.773 jiwa (34,97%) dan penduduk nonPapua sebanyak 166.932 (65,03%). Angka ini menunjukkan bahwa di Kota Jayapura, jumlah penduduk pendatang jauh lebih banyak daripada penduduk asli Papua. Istilah amber dan komin kemudian muncul yang menunjuk pada orang asli Papua (komin) dan kaum pendatang nonPapua (amber). Tingginya arus migrasi di Kota Jayapura mengakibatkan kemajemukan dalam struktur sosial budaya dan ekonomi penduduknya. Hal ini berdampak pula pada terbentuknya pola permukiman penduduk. Tulisan ini membahas mengenai heterogenitas etnis pada masyarakat Kota Jayapura dalam membentuk pola keruangan kota. Dari hasil pembahasan diketahui bahwa permukiman yang ada di Kota Jayapura terdiri dari permukiman penduduk asli setempat, permukiman campuran yang dihuni oleh penduduk Papua dan penduduk nonPapua, permukiman yang dihuni oleh etnis Papua dari luar Kota Jayapura dan permukiman yang dihuni oleh etnis pendatang nonPapua tertentu. Permukiman penduduk asli setempat masih tetap bertahan sebagai permukiman adat yang mempunyai makna religius spiritual yang harus dijaga dan dilindungi. Sedangkan permukiman penduduk pendatang Papua maupun nonPapua terbentuk berdasarkan beberapa preferensi, yaitu adanya ikatan kekerabatan, kedekatan dengan sumber mata pencaharian (tempat kerja) dan status sosial.